Proportion and factors affecting for post-natal care utilization in developing countries: A systematic review - Adhikari, Chiranjivi; Yadav, Rajesh Kumar; Timilshina, Purnima; Ojha, Renuka; Gaire, Deepika; Ghimire, Ashmita (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background: Majority of neonatal and maternal mortalities occur in developing countries. Moreover, around half of both mortalities occur in immediate postnatal period. Postnatal care utilization is aimed to reduce both mortalities and promote their health status. Methods: We searched PubMed, Google Scholar and HINARI between Jan 1, 2006 and Apr 31, 2014. Cross-sectional studies, surveys published in English language with finding of percentage of and factors affecting postnatal care utilization were included in the analysis. Weighted percentage with 95% CI was calculated to summarize the proportion. Odds ratio of minimum and maximum value was used to summarize associated factors. P-value <0.01 was taken as cut-off for significance of associated factors. Results: Of 45 accessed and reviewed full-text articles, nine included in the review. The studies were conducted in seven countries and total postnatal mothers in all samples were 49385. The weighted percentage of postnatal service utilization was 36.0 (95% CI, 22.5-49.5). Mother’s and husband’s higher educational level; higher wealth quintile of the family; occupation; mother’s age at last delivery; number of ANC visit; and number of pregnancy were found associated with postnatal care utilization. Conclusion: The data that only around one in every three mothers utilizing post-natal care shows that scaling-up and improving the service is imperative. The education including literacy programs for both mother and husband; scaling-up of 4th ANC visit; creating earning opportunities for mothers and focusing the mothers of 20-30 years age group would be some intervening areas, however, further evaluation and reviews from interventional designs are suggested before reaching the firm conclusion. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.14-19